Reactivity ratios estimation of the free-radical copolymerization of itaconic acid and n-vinyl-2-pyrrolidone by a non-linear regression technique using the error-in-variables methodology - Krieger, Bruno Vasconcellos (2020)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Química, Florianópolis, 2020.